Iraq Crude Oil Exports- January, February, March, April, May, June/ 2023 - SOMO, Oil Marketing Company (Journal of Petroleum Research and Studies, 2024)
Table 1. Iraq Crude Oil Exports – January 2023 Table 2. Iraq Crude Oil Exports – February 2023 Table 3. Iraq Crude Oil Exports – March 2023 Table 4. Iraq Crude Oil Exports – April 2023 Table 5. Iraq Crude Oil Exports – May 2023 Table 6. Iraq Crude Oil Exports – June 2023